Perbandingan Kewenangan Antara Badan Otorita Ibu Kota Nusantara dengan Badan Otorita Labuan Bajo dalam Penyelenggaraan Pemerintahan Indonesia - llham Al Barkah (Jurnal Hukum dan Sosial Politik, 2025)
This study aims to determine and analyze the comparison of authority and characteristics between the Nusantara Capital Authority and the Labuan Bajo Authority in the administration of the Indonesian government. The type of research used in the research on the comparison of the authority of the Nusantara Capital Authority Authority and the Labuan Bajo Authority in the Implementation of Indonesian Government is still the same as the initial research proposal, namely using the type of normative law research (normative law research) which is carried out by examining library materials or secondary data. Comparison of the authority between the Nusantara Capital Authority and the Labuan Bajo Authority, namely the authority of the Nusantara Capital Authority (IKN) is regulated in Law Number 3 of 2022 concerning the National Capital and further regulated through Government Regulation Number 27 of 2023 concerning the Special Authority of the Nusantara Capital, namely special authority related to granting investment licenses, ease of doing business, and providing special facilities to parties that support the implementation of the Indonesian Government, as well as the provision of special facilities to parties that support financing in the context of preparation, construction, and relocation of the National Capital, as well as the development of the Archipelago Capital and partner regions and authority in government affairs, while the authority of the Labuan Bajo Authority Agency